2002
DOI: 10.1046/j.1442-2042.2002.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum and prostatic zinc concentrations in rats after intraprostatic injection of zinc: Comparison of two forms of zinc delivery

Abstract: Background : We investigated changes in zinc concentrations in serum and prostatic tissue after an intraprostatic injection of zinc, and compared two forms of zinc delivery: solution and liposome. Methods : Ninety-six male Wistar rats were used in the study (24 controls, 72 test rats). The test animals were randomly divided into two groups and were injected intraprostatically with 2 mL of 0.04 mol/L zinc sulfate according to the form of zinc delivery. Nine rats in each test group were sacrificed 1 day, 7, 14 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Further studies from the same institution demonstrated that intraprostatic injection of zinc in normal rats increased and maintained prostatic zinc concentrations for 4 weeks and did not affect serum levels. 16 No human studies are yet available, but it would be interesting to see if there is any synergistic effect between zinc and potent antimicrobials.…”
Section: Intraprostatic Zinc Injectionmentioning
confidence: 99%
“…Further studies from the same institution demonstrated that intraprostatic injection of zinc in normal rats increased and maintained prostatic zinc concentrations for 4 weeks and did not affect serum levels. 16 No human studies are yet available, but it would be interesting to see if there is any synergistic effect between zinc and potent antimicrobials.…”
Section: Intraprostatic Zinc Injectionmentioning
confidence: 99%